2020
DOI: 10.3390/su12093835
|View full text |Cite
|
Sign up to set email alerts
|

Public Perspective on Increasing the Numbers of an Endangered Species, Loggerhead Turtles in South Korea: A Contingent Valuation

Abstract: The loggerhead turtle is one of the representative endangered marine species in South Korea. Thus, the country’s government is trying to push ahead with a project to increase the number of loggerhead turtles through the research and development of technology to hatch them artificially and release them into the wild. This article attempts to investigate the public perspective on the project using contingent valuation (CV). To this end, a CV survey of one thousand households across the country was implemented us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The parks offer leisure to inhabitants and serve as a traveler's destination for non-inhabitant visitors. Therefore, recreational parks and forests offer numerous benefits and services: psychological, physical, aesthetic, economic, environmental, social, as well as cultural, recreational, and historical [33][34][35][36][37][38][39][40][41][44][45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The parks offer leisure to inhabitants and serve as a traveler's destination for non-inhabitant visitors. Therefore, recreational parks and forests offer numerous benefits and services: psychological, physical, aesthetic, economic, environmental, social, as well as cultural, recreational, and historical [33][34][35][36][37][38][39][40][41][44][45][46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the study can be replicated elsewhere with some improvements as suggested in this study. Additionally, there are some studies necessary for the methodology support on forest ecosystems services valuation and conservation efforts [28,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were collected by an online survey. Commonly used survey methods include telephone surveys, mail surveys, face-to-face interviews, and online surveys [36]. Since some of them have limits to use such as difficulty in explanation without visible information for phone surveys, the low response rate for email surveys, and high costs for face-toface interviews, their uses have been decreasing.…”
Section: Data Collectionmentioning
confidence: 99%
“…Most of the respondents' monthly household income is less than CNY 5000, accounting for 68.7% of the sample. The data were selected randomly, which is necessary to verify the representativeness of the sample [36,38]. Table 2 shows a comparison of some substantial socio-economic characteristics of the sample and those of the population, and it is found that there is not much difference between them.…”
Section: Socio-economic Characteristicsmentioning
confidence: 99%